Development of rainfall-runoff-sediment discharge relationship in the Blue Nile Basin - Fetene, F.; Awulachew, Seleshi Bekele; Teklie, N. (2009)
The Blue Nile (Abbay) Basin lies in the western part of Ethiopia between 70 45'-120 45' N and 340 05'-390 45' E. The Blue Nile region is the main contributor to flood flows of the Nile, with a mean annual discharge of 48.5 km3. Soil erosion is a major problem in Ethiopia. Deforestation, overgrazing, and poor land management accelerated the rate of erosion. The SWAT was successfully calibrated and validated for measured streamflow at Bahir Dar near Kessie and at the border of Sudan for flow gauging stations, and for measured sediment yield at Gilgel Abbay, Addis Zemen and near Kessie gauging stations in the Blue Nile Basin. The model performance evaluation statistics (Nash?Sutcliffe model efficiency (ENS) and coefficient of determination (r?)) are in the acceptable range (r2 in the range 0.71 to 0.91 and ENS in the range 0.65 to 0.90). It was found that the Guder, N. Gojam and Jemma subbasins are the severely eroded areas with 34% of sediment yield of the Blue Nile coming from these subbasins. Similarly, the Dinder, Beshilo and Rahad sub basins only cover 7% of sediment yield of the basin. The annual average sediment yield is 4.26 t/ha/yr and the total is 91.3 million tons for the whole Blue Nile Basin in Ethiopia.